Memes as Means: Using Popular Culture to Enhance the Study of Literature - Pamela Hartman; Jessica Berg; Hannah R. Fulton; Brandon Schuler (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
Artistic response is the process by which readers create concrete representations of their transactions with a text through artistic means, including visual arts (e.g. drawing, sculpture, and painting), drama, and music. Research has shown that artistic response helps students form meaningful relationships with texts, as it is a tool that encourages students to enter, explore, make connections, and enjoy stories and characters. In this article we describe an artistic response strategy that we developed and implemented. Recognizing that today’s students often know and interact with the world through social media and memes, we draw on this cultural tool to leverage the power of this platform and its familiarity and appeal to our students
Keywords: English Language Arts; Literature